2014
DOI: 10.1016/j.snb.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption/combustion-type gas sensors employing mesoporous γ-alumina loaded with core(Au)/shell(Pd) nanoparticles synthesized by sonochemical reduction

Abstract: Adsorption/combustion-type gas sensors employing mesoporous γ-alumina (mp-Al2O3) powders loaded with core(Au)/shell(Pd) nanoparticles, which were synthesized by sonochemical reduction, (n(Au/Pd)/mp-Al2O3, n: the amount of Au/Pd nanoparticles loaded, Pd loaded onto the mp-Al2O3 powders was reduced (≤ 0.5 wt%). These sensing properties seem to be largely dependent on the morphological and compositional characteristics of Au and Pd loaded on the γ-alumina surface. In addition, the n(Au/Pd)/mp-Al2O3 sensors showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The core/shell structure was completely destroyed after the heat treatment at 700 • C for 2 h in air and most of Au agglomerated as a large particle with a diameter of 20-25 nm, but the size of Pd (actually, PdO in air) nanoparticles remained almost unchanged and Pd nanoparticles were highly dispersed on the oxide surface with a small amount of Au. Therefore, we discussed that the highly-dispersed Pd-based nanoparticles and the relatively-large Au-based particles on the mp-Al 2 O 3 powder improved the catalytic combustion properties of the VOCs adsorbed on the oxide surface and the thermal conductivity, respectively, in the previous study [33].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The core/shell structure was completely destroyed after the heat treatment at 700 • C for 2 h in air and most of Au agglomerated as a large particle with a diameter of 20-25 nm, but the size of Pd (actually, PdO in air) nanoparticles remained almost unchanged and Pd nanoparticles were highly dispersed on the oxide surface with a small amount of Au. Therefore, we discussed that the highly-dispersed Pd-based nanoparticles and the relatively-large Au-based particles on the mp-Al 2 O 3 powder improved the catalytic combustion properties of the VOCs adsorbed on the oxide surface and the thermal conductivity, respectively, in the previous study [33].…”
Section: Introductionmentioning
confidence: 95%
“…The addition of thermally conductive ␣-Al 2 O 3 powders to the sensor materials was also effective in improving the ethanolsensing properties [32]. In addition, the high-dispersed loading with core(Au)/shell(Pd) nanoparticles on the mp-Al 2 O 3 powder by utilizing sonochemical reduction of Au and Pd chlorides with polyethylene glycol monostearate drastically enhanced the sensing properties to ethanol, toluene and n-hexane of the adsorption/combustion-type gas sensors [33]. The core/shell structure was completely destroyed after the heat treatment at 700 • C for 2 h in air and most of Au agglomerated as a large particle with a diameter of 20-25 nm, but the size of Pd (actually, PdO in air) nanoparticles remained almost unchanged and Pd nanoparticles were highly dispersed on the oxide surface with a small amount of Au.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has actually demonstrated that catalytic combustion-type gas sensors that were operated in a mode of pulsed temperature heating (typical pulsed-heating period: 400 ms for 10 s), so-called adsorption/combustion-type gas sensors, showed large dynamic responses to various types of VOCs. (35)(36)(37)(38)(39)(40) In this work, we have attempted to improve the acetonesensing properties of WO 3 -based sensors, particularly in wet air, by the loading of noble metal and/ or NiO onto the surface of WO 3 , as well as by operation in dynamic temperature modulation mode. 3 powders loaded with and without noble metal and/or NiO HNO 3 aq.…”
Section: Introductionmentioning
confidence: 99%